1997
DOI: 10.1007/bf03217308
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of primary school children’s abilities and strategies for reading and recording time from analogue and digital clocks

Abstract: Sixty-seven children in Grades 1-3 and 66 children in Grades 4-6 were tested for their ability to read and record analogue and digital times. The children in Grades 4-6 were asked to describe their strategies. A sequence of time acquisition was proposed, based on a recent theory of cognitive development and the literature. This was: hour, half hour, quarter hour, five minute, and minute times. Times after the hour would be more difficult and digital times would be learned sooner. The sequence was confirmed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
3
16
0
4
Order By: Relevance
“…The results of the present study show that Flemish children indeed acquire clock reading skills according to the previously described age-related stages: hour times are mastered at the age of six, half hour times at the age of seven, five minute times at the age of nine and one minute clock times become accurate from the age of eleven, which is even later than suggested by previous studies (e.g., Boulton-Lewis, et al, 1997;Case, 1992;Case, et al, 1986;Friedman & Laycock, 1989). Chinese children, on the other hand, acquire complex clock reading skills, i.e.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The results of the present study show that Flemish children indeed acquire clock reading skills according to the previously described age-related stages: hour times are mastered at the age of six, half hour times at the age of seven, five minute times at the age of nine and one minute clock times become accurate from the age of eleven, which is even later than suggested by previous studies (e.g., Boulton-Lewis, et al, 1997;Case, 1992;Case, et al, 1986;Friedman & Laycock, 1989). Chinese children, on the other hand, acquire complex clock reading skills, i.e.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have continuously built upon the premise that learning to read the clock is mainly a matter of maturation (Levin & Gilat, 1983;Piaget, 1969;Siegler & Richards, 1979). In light of this assumption, early studies suggested a number of age-related stages in children"s development of clock reading skills, stating that children can read hour times at the age of six, half hour times at the age of seven, five minute clock times at the age of eight or nine and one minute times at the age of ten (Boulton-Lewis, et al, 1997;Case, 1992;Case, et al, 1986;Friedman & Laycock, 1989). These age-related stages have been adopted in the educational practice for clock reading in many western countries, such as Belgium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hours of a day are a special domain, as observers are trained to read the hours from radial clocks from an early age [9,25]. It is therefore possible that familiarity with the radial clock design facilitates a more efficient cognition of daily patterns in the underlying data when visualizing the data with a radial clock-like layout.…”
Section: Introductionmentioning
confidence: 99%
“…When considering digital and analog time telling, it has been found that a digital format was easier to read when assessed in typically developing children (Boulton‐Lewis, Wilss, & Mutch, ). Additionally, digital clocks are found on everyday items (e.g., cell phones, televisions, microwaves) across environments.…”
Section: Introductionmentioning
confidence: 99%